The Role of Dividend Policy in Preventing Tax-Induced Earnings Management: Empirical Evidence from Public Manufacturing Companies in Indonesia - Cliff Oliver Winoto; Yuniarwati Yuniarwati (Eduvest - Journal of Universal Studies, 2025)
Tax rate reductions can encourage companies to engage in earnings management practices. However, corporate governance mechanisms such as dividend distribution have the potential to prevent earnings management practices. This study aims to test the ability of dividend policy to prevent tax-induced earnings management. Earnings management is measured using the Modified Jones Model by calculating the value of discretionary accruals. While tax rates are measured using the effective tax rate. This study uses data from 2016 to 2019 to estimate discretionary accruals and uses only 2019 data for hypothesis testing. This study finds tax induced earnings management carried out by manufacturing companies in Indonesia during the transition year before the tax rate reduction. Companies implement downward earnings management as a form of intertemporal income shifting. These results are in line with Agency Theory by providing empirical evidence of tax-book trade-offs that sacrifice shareholder interests. Meanwhile, dividend policy does not have a significant impact and fails to mitigate earnings management practices during the transition period.